Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jgr.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and identification of ginsenoside structural isomers by two-dimensional mass spectrometry combined with statistical analysis

Abstract: Background In the current phytochemical research on ginseng, the differentiation and structural identification of ginsenosides isomers remain challenging. In this paper, a two-dimensional mass spectrometry (2D-MS) method was developed and combined with statistical analysis for the direct differentiation, identification, and relative quantification of protopanaxadiol (PPD)-type ginsenoside isomers. Methods Collision-induced dissociation was performed at successive collis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Ginsenoside M1 and ginsenoside Rh2 are the major ginsenoside metabolites with anticancer activities [ 25 ]. In addition, ginsenoside M1 and ginsenoside Rh2 are positional isomers [ 26 ], therefore, we investigated the effect of ginsenoside M1 and ginsenoside Rh2 in human oral cancer cells. Human oral cancer cells SAS and OEC-M1 were plated at 5 × 10 5 cells per 6-cm dish in 2 mL of culture medium and were grown overnight at 37 °C in a 5% CO 2 incubator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenoside M1 and ginsenoside Rh2 are the major ginsenoside metabolites with anticancer activities [ 25 ]. In addition, ginsenoside M1 and ginsenoside Rh2 are positional isomers [ 26 ], therefore, we investigated the effect of ginsenoside M1 and ginsenoside Rh2 in human oral cancer cells. Human oral cancer cells SAS and OEC-M1 were plated at 5 × 10 5 cells per 6-cm dish in 2 mL of culture medium and were grown overnight at 37 °C in a 5% CO 2 incubator.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ginsenoside M1 and ginsenoside Rh2 showed different killing effect in normal gingival epithelioid SG cells. As ginsenoside M1 and ginsenoside Rh2 are positional isomers [ 26 ], we suggested that the different killing effect of ginsenoside M1 and ginsenoside Rh2 on normal gingival epithelioid SG cells may be structurally selective. Although ginsenoside M1 was less toxic to human gingival epithelioid SG cells than ginsenoside Rh2, ginsenoside M1 showed a similar killing effect in OEC-M1 cells and SG cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some ginsenosides, such as Rg2, Rg3, Rh1, and Rh2, exist in different stereoisomeric forms, 20-(S) and 20-(R), depending on the position of the hydroxyl group in C-20. Other ginsenosides, including Rb2, Rb3, Rc, aglycone, Rg1, and F11, contain different saccharide substituents [ 41 , 42 ]. However, not all ginsenosides occur naturally in ginseng.…”
Section: Components Of Ginsengmentioning
confidence: 99%
“…It is very important to quantitate the constitutional and stereisomeric isomer of ginsenosides independently because each isomer was known to have different activity [10][11][12]. Analysis of ginsenoside isomers required the derivatization for GC analysis [13] or 2-dimensional UHPLC-MS/MS for the separation [14]. Separating isomers using MS detection is challenging due to the similarity of the MS spectra and MRM transition between isomers.…”
Section: Separation Of 26 Ginsenosides Including Isomers On Various Analytical Columnsmentioning
confidence: 99%